GIS-Based Modelling and Multi-Criteria Evaluation for the Suitability Assessment of Green Mussel Aquaculture Expansion in Tagabuli Bay, Southeastern Mindanao - Aljhun Lloyd A. Barranco; Marjel M. Broce; Harvey D. Lobo; Rodceal Malinao; Honielyn Taka; Adzel Adrian G. Baldevieso; Kaent Immanuel N. Uba; Fiona L. Pedroso; Fernand F. Fagutao (Thalassas: An International Journal of Marine Sciences, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Hydrodynamics of rainfall peaks in homogeneous regions clustered using the K-means algorithm in Central Africa - Fernand L. Mouassom; Alain T. Tamoffo; Elsa Cardoso-Bihlo (Climate Dynamics, 2025)

Efficiency of the green mussel, Perna viridis (Linnaeus, 1758) to bioremediate total heterotrophic bacteria, Vibrio and Plankton in the culture medium of the tiger shrimp Penaeus monodon pond system - Elgen M. Arriesgado; Dan M. Arriesgado; Fernand F. Fagutao; Cassiano H. Choresca; Gwen M. Anuevo; Jomar F. Besoña; Marnelle B. Sornito; Fiona L. Pedroso (Aquaculture International, 2025)

Analysis of air temperature anomalies during abnormal rainfall events in Western Central Africa from September to November 2023 - Brice C. Tchana; Zéphirin Y. Djomou; Kevin Kenfack; Alain T. Tamoffo; Fernand L. Mouassom; Lucie A. Djiotang Tchotchou; Derbetini A. Vondou; César B. Mbane (Theoretical and Applied Climatology, 2025)

Machine learning assisted identification of sea surface temperature patterns related to extreme rainfall events over Cameroon - Fernand L. Mouassom; Edwine Tendong; Alain T. Tamoffo (Theoretical and Applied Climatology, 2025)

Extremes events and socio-economic impacts in central Africa: a CMIP6-based analysis of projections - Dorcas Daniella Ebedi-Nding; Alain T. Tamoffo; Fernand L. Mouassom (Modeling Earth Systems and Environment, 2024)

Understanding the environmental conditions of the extreme precipitation event on June 20, 2015, in the city of Douala, Cameroon - Fernand L. Mouassom; Alain T. Tamoffo (Natural Hazards, 2024)

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

The contribution of ‘chitoumou’, the edible caterpillar Cirina butyrospermi, to the food security of smallholder farmers in southwestern Burkina Faso - Charlotte L. R. Payne; Athanase Badolo; Sioned Cox; Bakary Sagnon; Darja Dobermann; Charlotte Milbank; Pete Scarborough; Antoine Sanon; Fernand Bationo; Andrew Balmford (Food Security, 2020)
Edible insects have been advocated as a means to combat food insecurity, which is prevalent in West Africa. In this study we look at the contribution of the shea caterpillar Cirina butyrospermi, colloquially known as ‘chitoumou’, to the food security of smallholder households in rural southwestern Burkina Faso. We used a mixed methods approach to understand the relationship between caterpillar collection, consumption, and sale by smallholder households, and their seasonal food security status. We found that caterpillars are an important source of food and income for households, significantly increasing the household consumption of animal protein and, with shea nuts, representing the main income source for the majority of women. We also found that food security is higher during caterpillar season, and that household-level food security during this season can be predicted by the amount of caterpillars collected, consumed and sold. However, this relationship holds only during the caterpillar season, suggesting that the positive impact of caterpillars on food security is temporally limited. We conclude that the shea caterpillar is an example of an edible insect that is crucial for seasonal food security in a widespread agricultural system.

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

Thin layers of Pseudo‐nitzschia spp. and the fate of Dinophysis acuminata during an upwelling‐downwelling cycle in a Galician RÃa - L. Velo Suárez; S. González Gil; P. Gentien; M. Lunven; C. Bechemin; L. Fernand; R. Raine; B. Reguera (Limnology and Oceanography, 2008)
Fine‐resolution measurements of phytoplankton and physical parameters were made from 31 May to 14 June 2005 in the Ría de Pontevedra (Spain), which is subject to seasonal upwelling. The main objective of this work was to elucidate physical‐biological interactions leading to subsurface aggregations of toxin‐producing microalgae ( Pseudo‐nitzschia spp. and Dinophysis spp.). A sequence of upwelling‐relaxation‐upwelling‐downwelling events was recorded with a moored Acoustic Doppler Current Profiler (ADCP). Thin layers (TLs) of Pseudo‐nitzschia spp. and other diatoms (up to 30 µg chlorophyll a L −1 ) developed and persisted in the pycnocline above cooler (12.5ºC) upwelled water but were vertically displaced and even dispersed during downwelling. The establishment of steep pycnoclines after upwelling pulses and the formation of TLs of Pseudo‐nitzschia spp. and other diatoms suggest that pycnoclines may act as retention areas for these populations. Their vertical displacement during downwelling would explain different patterns observed in the contamination of benthic resources and raft‐mussels. A decimeter‐scale segregation of Pseudo‐nitzschia micans and Dinophysis acuminata populations was observed. The population of D. acuminata , present since March 2005 in Ría de Pontevedra, was never found within the pycnocline, did not perform any significant vertical migration, and was not dispersed during upwelling. Instead, it formed patches (up to 8 × 103 cell L −1 ) in the warmer (15‐18ºC) surface (0‐4 m) waters associated with a diurnal thermocline, and it spread throughout the ría into a near‐surface layer during relaxation and downwelling. These results demonstrate the importance of considering species‐specific behavior to predict the location of cell maxima.

Does the western Irish Sea gyre influence the distribution of pelagic juvenile fish? - M. Dickey‐Collas; J. Brown; L. Fernand; A. E. Hill; K. J. Horsburgh; R. W. Garvine (Journal of Fish Biology, 1997)
The western Irish Sea is an important spawning and nursery ground for many commercially exploited fish. Spawning begins in the Irish coastal regions in early spring, and moves offshore as the season develops. As a result of the onset of seasonal heating in spring, stratification isolates a dome of cold bottom winter water in the deep (>100 m) basin of the western Irish Sea. The resultant density fields drive a cyclonic gyre which dominates the circulation of the region during late spring and summer and is characterized by anticlockwise current speeds which exceed 0.2 ms –1 , after removal of tides. Surveys of pelagic juvenile (0‐group) fish in 1994, 1995 and 1996, showed that they were coincident with the centre of the gyre. Physical data from 1994 and 1995, were used to describe the horizontal and vertical structure of the water column and the associated circulation regime. The behaviour and swimming speeds of pelagic juvenile fish were insufficient to explain their apparent shift in abundance away from the coast to the central western Irish Sea. Drifter and current data suggested that their entrainment into the gyre could provide both the transport and retention mechanisms.

Interactions between adjacent fibers in a cardiac muscle bundle - Sining Wang; L. Joshua Leon; Fernand A. Roberge (Annals of Biomedical Engineering, 1996)

Propagation on a central fiber surrounded by inactive fibers in a multifibered bundle model - Fernand A. Roberge; Sining Wang; Hervé Hogues; L. Joshua Leon (Annals of Biomedical Engineering, 1996)